Assessment of Perinatal Care Satisfaction Amongst Mothers Attending Postnatal Care in Ibadan, Nigeria - Titilayo Dorothy Odetola; Emmanuel Oluwabukunmi Fakorede (Ubiquity Press, 2018)
Introduction: Patient satisfaction has been identified as a major index in the assessment of quality of healthcare globally. Mothers judge the quality of perinatal care received based on their satisfaction with the services provided, thus influencing their utilization of the available health facilities. There is currently a dearth of literature on users' satisfaction of services rendered at the primary level of care, which is the first port of call to the health system aimed at serving majority of the populace. Objectives: The study was set out to investigate maternal satisfaction with perinatal care received in selected primary health centres in Ibadan. Methods: The study was a cross-sectional survey involving 66 women receiving postpartum care from five randomly selected primary health centres in Ibadan north-west local government using a 72-itemed questionnaire with p < 0.05. Findings: The majority of the respondents (98.5%) perceived the perinatal care they received as high quality, and 94% and 98% were satisfied with services and facilities used for their care, respectively. Identified causes of dissatisfaction included dirty hospital environment, inadequate water supply and hospital facilities, distance of hospital location, cost of materials, time wasting, inadequate staffing and poor attitude, and verbal and physical abuse. An association exists between maternal satisfaction with quality of care and future intention for subsequent utilization (χ2 = 13.306; p = 0.0001). Conclusion: The overall maternal satisfaction on the perinatal care provided was perceived as very good. However, few domains of dissatisfaction were identified that would need to be addressed by healthcare professionals and policymakers to sustain and improve utilization of orthodox health care services amongst mothers, thereby contributing to achieving the third Sustainable Development Goal.